2012
DOI: 10.5194/bg-9-973-2012
|View full text |Cite
|
Sign up to set email alerts
|

Insignificant enhancement of export flux in the highly productive subtropical front, east of New Zealand: a high resolution study of particle export fluxes based on <sup>234</sup>Th: <sup>238</sup>U disequilibria

Abstract: Abstract. We evaluated the export fluxes of Particulate Organic Carbon (POC) in the Subtropical Frontal zone (STF) of the SW Pacific sector of the Southern Ocean. The site is characterized by enhanced primary productivity, which has been suggested to be stimulated through so-called natural iron fertilization processes where iron-depleted subantarctic water (SAW) mixes with mesotrophic, iron-replete subtropical water (STW). We adopted the small-volume 234 Th method to achieve the highest possible spatial sampli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Non-steady-state effects of 234 Th profiles on export fluxes will not be considered further because we do not have Lagrangian observations at multiple time points necessary to detect such effects (Buesseler et al, 2003;Resplandy et al, 2012). et al, : Shimmield et al, 1995Rutgers Van Der Loeff et al, 1997Buesseler, 1998;Cochran et al, 2000;Buesseler et al, 2001Buesseler et al, , 2003Friedrich and van der Loeff, 2002;Coppola et al, 2005;Morris et al, 2007;Thomalla et al, 2008;Savoye et al, 2008;Rodriguez y Baena et al, 2008;Jacquet et al, 2011;Zhou et al, 2012;Planchon et al, 2013). By contrast, the POC fluxes we report (4.5 ± 3.9 mmol m −2 d −1 ) are on average 3 times lower than fluxes from other studies (12.6 ± 13.3 mmol m −2 d −1 ) due to lower POC : 234 Th ratios measured in > 51 µm particles.…”
Section: Choice Of Export Depthmentioning
confidence: 99%
“…Non-steady-state effects of 234 Th profiles on export fluxes will not be considered further because we do not have Lagrangian observations at multiple time points necessary to detect such effects (Buesseler et al, 2003;Resplandy et al, 2012). et al, : Shimmield et al, 1995Rutgers Van Der Loeff et al, 1997Buesseler, 1998;Cochran et al, 2000;Buesseler et al, 2001Buesseler et al, , 2003Friedrich and van der Loeff, 2002;Coppola et al, 2005;Morris et al, 2007;Thomalla et al, 2008;Savoye et al, 2008;Rodriguez y Baena et al, 2008;Jacquet et al, 2011;Zhou et al, 2012;Planchon et al, 2013). By contrast, the POC fluxes we report (4.5 ± 3.9 mmol m −2 d −1 ) are on average 3 times lower than fluxes from other studies (12.6 ± 13.3 mmol m −2 d −1 ) due to lower POC : 234 Th ratios measured in > 51 µm particles.…”
Section: Choice Of Export Depthmentioning
confidence: 99%
“…The second counting rate of particulate 234 Th is generally overlooked due to its constant value of 0.3–0.4 counts per minute (cpm)121314. In this study, RA P234 was calculated (see Appendix A1–A3), and data at selected stations are depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4. In the open ocean, the second counting rate of particulate 234 Th (n P2 ) was relatively stable with a value of 0.3~0.4 cpm, which also depends on the instrumental background with a normal value of 0.15~0.2 cpm via gas-flow proportional low-level RISØ β-counter (Model GM-25-5, RISØ National Laboratory, Denmark)121314. In this study, the abnormally high second counting rate of particulate 234 Th was observed for bottom seawater on the continental shelf in the western Arctic Ocean.…”
Section: Methodsmentioning
confidence: 99%
“…Since 1969 (Matsumoto, ), 234 Th activity has been measured by tens of oceanographic cruises. The data set used in this study (detailed in supporting information Data Set S1) includes data from the literature (Amiel et al, ; Buesseler et al, , ; Charette & Moran, , Charette et al, ; Coale & Bruland, ; Coppola et al, ; Jacquet et al, ; Kawakami & Honda, ; Knauss et al, ; Moran et al, ; Morris et al, ; Murray et al, ; Roca‐Martí et al, ; Rodriguez y Baena et al, ; Santschi et al, ; Shimmield et al, ; Thomalla et al, ; Zhou et al, ), PANGAEA data publisher (Buesseler, , , ; Cochran & Cochran, ; Coppola & Jeandel, ; JGOFS‐INDIA, , ; Moran et al, ; Roca‐Martí et al, ; Rutgers van der Loeff, ; Young & Murray, ), and five GEOTRACES cruises whose data are reported in the Intermediate Data Product 2014 (Mawji, ): GA02 (Owens et al, ) in the western Atlantic, GA03 (Owens et al, ) from the United States to Cape Verde to Portugal, GIPY11 (Cai et al, ) in the Arctic Ocean, and GIPY4 (Planchon et al, ) and GIPY5 (Rutgers van der Loeff et al, ) in the Atlantic sector of the Southern Ocean. In a near future, GEOTRACES data from all major oceanic basins should be available.…”
Section: Methodsmentioning
confidence: 99%